Awareness of Climate Change Through Social Media Platform: A Case of Khyber Pakhtunkhwa (Journal of Asian Development Studies, 2025)
The issue of climate change is rapidly becoming a serious and complex problem in Pakistan. The country has been experiencing the deterioration of its condition for many years. Although those in charge of government policies and attorneys have made efforts to mitigate these threats, in several aspects, they have not been very effective. This is primarily because individuals lack sufficient knowledge about climate literacy (Jan et al., 2020). This paper examines the current state of climate change awareness in KPK, as well as the role of social media and social activists in promoting environmental awareness and media literacy. The results, which were the outcome of a qualitative, descriptive, and analytical approach to the study, demonstrated that a general lack of awareness of climate-related problems among the population is a significant drawback to the effectiveness of these undertakings. The social media campaign on environmental awareness needs to be initiated by the people themselves, rather than by policymakers or elites. Climate literacy should be promoted using readily available methods, such as social media. The report emphasises the need for nationwide plans to increase knowledge about climate change and media literacy, aiming to equip local communities with the necessary tools to address the pressing climate problem.